Navnet i centrum: Om placeringsdiskurs og forskellen imellem navne i tale og skrift - Sandst, Line (Studier i Nordisk, 2022)
In this article, I discuss how linguistic ambiguity arises and differs in spoken and written language situations in linguistic landscapes (LL). I investigate overall language comprehension, word formation and homonymy in order to understand why uncertainties occur and how language users can determine what is meant in a given context. In doing so, I suggest the necessity to distinguish between the spoken and written contexts of proper names in order to interpret a given name. I investigate the different modalities available and used in spoken and written name forms, respectively, and I clarify the importance of the discourse for placement of proper names as an important factor for distinguishing between proper names and other grammatical categories in LL.